The growth, development and impact of the Grahamstown Festival of the Arts with special reference to music - Silva, Jane Susan (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 1998)
The Grahamstown Festival has become a huge and complex annual celebration of the arts, transforming the small Eastern Cape city for ten days every year. However this event had very modest beginnings, as did music and festivals in the city of Grahamstown. From its early days Grahamstown showed strong signs of becoming an important cultural centre, presenting numerous musical concerts from 1812, the festival tradition in the city beginning in 1887. The modern arts festival, initiated in 1971, had a chequered history during the early and mid 1970's, weathering economic recession, petrol restrictions and a repressive and restrictive political atmosphere. However by 1979 the event had become established and popular enough to ensure continued success during the 1980's. The period 1980-89 was one of great growth and development for the festival regarding attendance, and the number and nature of productions presented. Music had always been an integral part of the festival, and for the first time its role in this artistic celebration is being examined. The impact of such an event is varied and far-reaching, and thus difficult to assess, but the thesis ends with an attempt to gauge the Festival's impact.
Keywords: Standard Bank National Arts Festival -- Grahamstown; Standard Bank National Arts Festival -- Influence; Grahamstown (South Africa) -- Art and music; Music -- South Africa -- Eastern Cape -- Grahamstown